Area‐Selective Growth of HfS2 Thin Films via Atomic Layer Deposition at Low Temperature. Issue 23 (19th October 2020) - Cao, Yuanyuan; Wähler, Tobias; Park, Hyoungwon; Will, Johannes; Prihoda, Annemarie; Moses Badlyan, Narine; Fromm, Lukas; Yokosawa, Tadahiro; Wang, Bingzhe; Guldi, Dirk M.; Görling, Andreas; Maultzsch, Janina; et al.
Abstract: The transition‐metal dichalcogenide HfS2 is a promising alternative semiconductor with adequate band gap and high carrier mobility. However, a controllable growth of continuous HfS2 films with selectivity for specific surfaces at a low temperature on a large scale has not been demonstrated yet. Herein, HfS2 films are grown at 100 °C by atomic layer deposition (ALD) based on the precursors tetrakis(dimethylamido)hafnium and H2 S. In situ vibrational spectroscopy allows for the definition of the temperature range over which (Me2 N)4 Hf chemisorbs as one monolayer. In that range, sequential exposures of the solid surface with (Me2 N)4 Hf and H2 S result in self‐limiting reactions that yield alternating surface termination with dimethylamide and thiol. Repeating the cycle grows smooth, continuous, stoichiometric films of thicknesses adjustable from angstroms to >100 nm, as demonstrated by spectroscopic ellipsometry, XRR, AFM, UV–vis and Raman spectroscopy, XPS, and TEM. The well‐defined surface chemistry enables one to deposit HfS2 selectively using, for example, patterns generated in molecular self‐assembled monolayers. This novel ALD reaction combines several attractive features necessary for integrating HfS2 into devices. Abstract : The 2D semiconductor hafnium sulfide, HfS2, is deposited for the first time using atomic layer deposition in mild conditions and low temperature (100 °C). The surface reactions are specific and allow for area‐selective deposition of high‐quality thin films on self‐assembled molecular monolayers. When properly protected from air, the material is pure, stoichiometric, and ordered on a short range as deposited.